If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4l + 12 = 8l Reorder the terms: 12 + 4l = 8l Solving 12 + 4l = 8l Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-8l' to each side of the equation. 12 + 4l + -8l = 8l + -8l Combine like terms: 4l + -8l = -4l 12 + -4l = 8l + -8l Combine like terms: 8l + -8l = 0 12 + -4l = 0 Add '-12' to each side of the equation. 12 + -12 + -4l = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -4l = 0 + -12 -4l = 0 + -12 Combine like terms: 0 + -12 = -12 -4l = -12 Divide each side by '-4'. l = 3 Simplifying l = 3
| 25x+5+5x=40-5 | | p=8l+12 | | 1/2(8h) | | 7y-3z=61 | | 2x^3+18x^2+36=0 | | -9=4+h | | 2y-5z=5 | | 2m=56 | | 2X+11+4X-3=180 | | s=180(4y-2) | | -2x-4(-3x-14)=-54 | | X+4z=13 | | log(3x)=2.1 | | 56x+56=42x+42 | | 2=18-4 | | 2n^2+7=-4n+5 | | y=x-19/-6 | | 4logx=-12 | | 76+28x=18x-4 | | 2=-x+3x^2 | | 2pir=88 | | X=1/2(105) | | 10y-4=y+6 | | (2n+12)= | | 4x^2-8+25=81 | | 6(2x+y)+2y-12x= | | -107=7x+6(3x+3) | | 2d^2-32=-32 | | 8.3=3-2.5c | | 17p=3 | | x^2-13x+42.25= | | 312.8z+(kz^2)=37223 |